(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Experiments were performed with mature embryos of four rice mutants for in vitro callus induction and plant regeneration. Different concentrations of 2,4-D and BAP combined, Kn and NAA combined and MET were used to assess their effects on induction of callus, shoot and roots. Given concentrations of 2,4-D with BAP and rice mutants in vitro cultures showed that Y-1281 and Atomita-4 had produced the highest percentages of callus at 2 mgl-1 2,4-D with 0.5 mgl-1 BAP in both light and dark conditions. Similar results were obtained in terms of concentrations and genotypes when 2,4-D and BAP were used together. Combined 2,4-D and BAP treatments showed significantly higher callusing under light conditions (90%). For shoot and root regenerations, once again the mutant genotype Y-1281 produced the highest percentages of shoots and roots and it also showed highest root length. And 11 mgl-1 2,4-D, 0.5 mgl-1 NAA combined and 2.5 mgl-1 MET concentration resulted significantly the highest shoot and root regeneration. Keywords: Callus induction; Mature embryos; Plant regeneration; Root induction; Rice DOI: 10.3329/jbau.v7i1.4796 J. Bangladesh Agril. Univ. 7(1): 39-45, 2009